2017
DOI: 10.1016/j.brainres.2017.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal high sucrose intake affected learning and memory of aged rat offspring with abnormal oxidative stress and NMDARs/Wnt signaling in the hippocampus

Abstract: Maternal over-nutrition may predispose offspring to obesity, type 2 diabetes and other adult diseases. The present study investigated long-term impact of prenatal high sucrose (HS) diets on cognitive capabilities in aged rat offspring. The fasting plasma glucose concentration did not differ between the control and HS groups. However, the fasting plasma insulin and insulin resistance index values were significantly increased in HS offspring that showed abnormal glucose tolerance test. HS offspring exhibited inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…In the present study, increased glucose tolerance in the offspring was associated with maternal high sucrose intake, which is consistent with a previous report, and pancreatic islets were enlarged in the HC offspring compared with the CC offspring, despite the HOMA‐IR score remaining unchanged. However, prenatal high sucrose intake plus postnatal high sucrose intake caused smaller pancreatic islets in the HH group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, increased glucose tolerance in the offspring was associated with maternal high sucrose intake, which is consistent with a previous report, and pancreatic islets were enlarged in the HC offspring compared with the CC offspring, despite the HOMA‐IR score remaining unchanged. However, prenatal high sucrose intake plus postnatal high sucrose intake caused smaller pancreatic islets in the HH group.…”
Section: Discussionsupporting
confidence: 93%
“…An increasing amount of evidence indicates that adverse in utero environments can affect the growth and development of offspring later in life. Prenatal risk factors such as high salt, high sucrose, high fat, hypoxia, nicotine/smoke exposure, and malnutrition often cause short‐term and/or life‐long health problems in offspring . Thus, ascertaining whether postnatal lifestyle and nutritional intake mitigates or worsens the impacts of prenatal exposure is important and interesting research.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, certain types of perinatal compromise have been associated with decreased activity of the GRIN2B gene and subsequent deficits in hippocampal learning, which highlights the balancing role of GRIN2B expression for optimal neurodevelopment. In particular, high‐fat and high‐sucrose maternal diets in rats have both been shown to increase and decrease the expression of GluN2B in the amygdala and hippocampus, respectively, with an anxious‐phenotype being displayed during adolescence and long‐lasting cognitive deficits present in the F1 offspring . Prenatal hypoxia, a common consequence of intrauterine growth restriction, is also associated with decreased expression of GluN2B in the hippocampus and subsequent impaired cognitive ability as indicated by diminished performance in the Morris water maze of 6‐week‐old rats .…”
Section: Dysregulation Of Gabaergic and Glutamatergic Pathways In Dismentioning
confidence: 99%
“…Experimental investigations in animals indicated that uncontrolled diabetes mellitus was associated with morphological and functional alterations in the brain [12][13][14]. Hippocampus, a structure critical to cognitive processes, has been shown to undergo apoptotic cell death when subjected to hyperglycemic insult [15][16][17].…”
Section: Introductionmentioning
confidence: 99%